Giải phẫu so sánh động vật có xương sống - Kent, George C; Carr, Robert K. (Boston, 2008)
Includes bibliographical references and index
Keywords: Vertebrates -- Anatomy; Động vật có xương sống -- Giải phẫu học; Anatomy -- Comparative; Giải phẫu học -- So sánh